The Global Garden project: Imagining plant science. Issue 6 (13th September 2020) - Lee, Nicholas M.; Hodgson, Hannah E.; Hann, Chris; O'Driscoll, Mike; Stebbings, Samantha; Matthewman, Colette; Kent, Miriam; Rant, Jenni; Osbourn, Anne
Social Impact Statement: Plants are rich sources of drugs and other high‐value chemicals that are used by humans. Many of the plant species that produce important molecules grow in remote locations and have extensive histories of indigenous use. Global concerns about sustainable supply have in some cases led to the development of alternative methods for production using biotechnological approaches. Consideration of responsible stewardship and use of the world's plants and associated traditional knowledge for the greater human good are at the heart of the Convention on Biological Diversity and the recently implemented Nagoya Protocol. The development of fora that enable open discussion and exploration of issues relating to these aspects will be critical in endeavors to protect and preserve both the environment and present and future generations. Summary: Here, we investigate the application of cross‐disciplinary approaches to explore societal perceptions of plants and their uses, focusing on high‐value chemicals. The Global Garden project engages the public, researchers, and regulators in day‐long workshops that combine science, poetry, and visual arts practice to foster participants' skill in imagining and re‐imagining relationships between high‐value plant products, biotechnology, and social and ethical aspects of these. The project represents an intervention into discussions of science communications and public engagement, addressing the uses and benefits of arts‐based approaches to foster imaginative engagement with plant science. The workshop reported here began with real plant case studies and a discussion of the aims of scientists using them. Participants were invited to respond to the issues of relationships among plants, chemicals, and people raised by the case studies through poetry and visual artwork. The poems and artwork that were produced show variation in the participants' imaginings of plant science. They present distinctive visions of research and innovation and of the associated ethical and social implications. This type of forum, based on creative immersion, opens up opportunities for engaging with and exploring complex relations between plant biotechnology, society, and ethics. This article offers a reflection on the uses, challenges, and implications of arts‐based approaches to research communications and public engagement that disrupts traditional knowledge transfer structures. In doing so, we frame the project within science communication pedagogies and consider public engagement a form of pedagogy. Abstract : Plants are rich sources of drugs and other high‐value chemicals that are used by humans. Many of the plant species that produce important molecules grow in remote locations and have extensive histories of indigenous use. Global concerns about sustainable supply have in some cases led to the development of alternative methods for production using biotechnological approaches. Consideration of responsible stewardship and use of the world's plants and associated traditional knowledge for the greater human good are at the heart of the Convention on Biological Diversity and the recently implemented Nagoya Protocol. The development of fora that enable open discussion and exploration of issues relating to these aspects will be critical in endeavors to protect and preserve both the environment and present and future generations.